Zimbabwe : Challenges and Policy Options after Hyperinflation. (Departmental Papers; Departmental Paper ;, 2010)
This paper examines the challenges and policy options after hyperinflation in Zimbabwe. The paper reviews the pros and cons of alternative monetary regimes for Zimbabwe to succeed the current multicurrency system, which the authorities consider a temporary arrangement. The analysis suggests that some form of official dollarization has significant advantages. The paper also assesses competitiveness and external sustainability in debt-distressed Zimbabwe. It also makes a case for creating fiscal space for growth and development in post-hyperinflation Zimbabwe.